Threadbare - Ferris, Monica (Ferris, Monica. Needlecraft mystery., 2011)
In this needlecraft novel from author Monica Ferris, Betsy gets embroiled in an embroidery mystery. When an elderly homeless woman is found dead on the shore of Lake Minnetonka, she's wearing something that holds the key to her identity but also opens up a mystery. Embroidered on her blouse is her will, in which she bequeaths everything she owns to her niece Emily Hame, a member of the Monday Bunch at Betsy Devonshire's Crewel World needlework shop! Emily's aunt turns out to be the second homeless woman to be found dead under mysterious circumstances. It's up to Betsy to discover the common thread between the deaths, and to determine if a murderer may strike again.